Biogenic silica in the coastal plume of the Mississippi River - David M Nelson; Quay Dortch (PANGAEA, 1996)
The surface distributions of dissolved silicic acid, chlorophyll and diatom abundance were measured in the plume of the Mississippi River and adjacent waters during spring (late April and early May 1993) and summer (July 1992). In spring, the time of maximum river flow, there was an intense diatom bloom with a mean diatom abundance of 1.5 x 10**7 cells/l, more than an order of magnitude higher than in summer. Mixing curves of silicic acid concentration ([Si(OH)4]) versus salinity indicate that biological uptake within the river plume removed >99% of the Si(OH)4 supplied by the river in spring and 80 to 95% in summer. In spring [Si(OH)4] was occasionally depleted to <0.2 μM-among the lowest values ever reported from the ocean-with extensive depletion to >=0.5 μM over the shelf. In summer [Si(OH)4] was less severely depleted; the lowest measured was 0.93 μM and all others were >=2.4 μM. 30Si kinetic experiments were performed during both spring and summer to measure the degree to which the rate of Si uptake by the natural diatom assemblages was limited in situ by substrate availability. In spring the dependence of the specific uptake rate (V) on extracellular [Si(OH)4] conformed much more closely to the Michaelis-Menten saturation function than has been observed in past studies. Strong dependence of V on [Si(OH)4] was observed throughout the most Si(OH)4-depleted (<0.5 μM) region, where V was limited to 12 to 45% of the diatom assemblages extquotesingle maximum uptake rate (Vmax). Half-saturation concentrations for Si uptake (Ks) averaged 0.85 uM (range = 0.48 to 1.71; n = 7) in spring, with the lowest values equal to the lowest previously reported for natural diatom assemblages. There was only 1 station in summer where V was limited by [Si(OH)4], and at that station Ks was 5.3 μM-quite high in comparison with previous studies. At stations where V was limited by [Si(OH)4], in both spring and summer, Chaetoceros spp. were numerically dominant; where there was no Si limitation other diatoms, usually Skeletonema costatum, dominated. The data thus indicate strong Si limitation in spring, with diatom assemblages well adapted to low [Si(OH)4], but little or no Si limitation in summer. Historical data suggest that coastal Si(OH)4 depletion and Si limitation may be recent phenomena in the northern Gulf of Mexico, resulting from increasing [NO3-] and decreasing [Si(OH)4] in the Mississippi River during the past 30 to 50 yr.
Supplement to: Nelson, DM; Dortch, Q (1996): Silicic acid depletion in the plume of the Mississippi River and limitation of Si availability to diatoms in the northern Gulf of Mexico: evidence from kinetic studies in spring and summer. Marine Ecology Progress Series, 136, 163-178, https://doi.org/10.3354/meps136163